Prenatal Curcumin Administration Reverses Behavioral and Neurochemical Effects and Decreases iNOS and COX-2 Expressions in Ischemic Rat Pups. (29th December 2014) - Telles, Maria Valéria Leimig; Nobre, Maria Elizabeth Pereira; Alencar, Lucas Parente; de Siqueira, Keicy Parente; Borges, Ada Maria Farias Sousa; Tavares, Márnya Wellysa Leite; Alves, Isabelle Bernardo; Duarte, Lara Soares; de Lacerda, Natália Kelly Rodrigues; de Alcântara, Glaura Fernandes Teixeira; Scerni, Débora Amado; Neves, Kelly Rose Tavares; et al.
Abstract : The objectives were to evaluate alterations in ischemic rat pups, from dams administered with curcumin (25 and 50 mg/kg). Ten-day-old male pups were subjected or not (SO) to brain ischemia and reperfusion, for 1, 7, and 14 days (this last group was submitted to behavioral evaluation). After that, pups were euthanized for determinations of striatal DA and DOPAC in SO, ischemic from untreated (ICUD) or curcumin treated (ICTD) dams, as well as hippocampal immunohistochemistry assays for iNOS and COX-2 and cresyl violet staining. At the 14th postischemia day, the ICUD group showed increased locomotor activity and rearing behavior, which were reversed in ICTD animals. ICUD pups presented decreased striatal DA and DOPAC levels, relatively to SO, mainly at the 1st postischemia day, but also at the 7th and 14th days which were partially reversed in ICTD pups. A greater number of viable neurons were observed in ICTD, as related to the ICUD group. Ischemia increased iNOS and COX-2 expressions, in CA1 and CA3 areas, at the 1st, 7th, and 14th postischemia days, and these effects were minimized in ICTD pups. In conclusion, the prenatal curcumin treatment was shown to be neuroprotective where the drug anti-inflammatory and antioxidant effects probably play a role.